Strategi Komunikasi Politik Caleg PSI Lolos DPRD Kota Bandung di Pemilu 2019 - Silvanus Alvin (MUKASI: Jurnal Ilmu Komunikasi, 2022)
Every Indonesian citizen has the right to vote and be elected to politics. There is an understanding that individuals who want to run in elections must spend large amounts of money, ranging from hundreds of millions to billions of rupiahs. However, a unique phenomenon occurred in the 2019 Election, especially in the scope of the legislative election in Bandung City. One of the candidates from PSI named, Yoel Yosaphat managed to pass to the parliament by spending only Rp 3 million in campaign funds. This study seeks to find out empirically and in-depth the applied political communication strategies. This research is qualitative research with a case study approach. Data was collected utilizing in-depth interviews. An interesting finding from this research is that two factors have implications for Yoel's passage to parliament, with a total support of 3,321 votes. The first is the social capital that Yoel got through networks or social relations that had been built before he entered politics. The second is the financial capital used to operate the campaign by purchasing campaign props such as banners, business cards, and calendars. The reason is to attract public attention as well as provide political messages.